Gene Expression Profiling of the Shoot Meristematic Tissues in Woodland Strawberry Fragaria vesca - Li, Yongping; Feng, Jia; Cheng, Laichao; Dai, Cheng; Gao, Qi; Liu, Zhongchi; Kang, Chunying (Frontiers in Plant Science, 2019)
Fragaria vesca, a wild diploid strawberry, has recently emerged as a model for the cultivated strawberry and other members of the Rosaceae. Differentiation and maintenance of meristems largely determines plant architecture, flower development and ultimately fruit yield. However, in strawberry, our knowledge of molecular regulation of meristems in different developmental context is limited. In this study, we hand dissected three types of tissues than contain meristematic tissues corresponding to shoot apical meristem (SAM), flower meristem (FM), and receptacle meristem (REM), in F. vesca for RNA-seq analyses. A total of 3,009 differentially expressed genes (DEGs) were identified through pairwise comparisons. These DEGs were grouped into nine clusters with dynamic and distinct expression patterns. In these nine clusters, 336 transcription factor genes belong to 46 families were identified; some of which were significantly enriched in FM and REM such as the MADS-box family or in REM such as the B3 family. We found conserved and distinctive expression patterns of totally 149 genes whose homologs regulate flowering time or SAM, leaf, and flower development in other plant species. In addition to the ABCE genes in flower development, new MADS box genes were identified to exhibit differential expression in these different tissues. Additionally, the cytokinin and auxin pathway genes also exhibited distinct expression patterns. The Arabidopsis homeobox gene WUSCHEL (WUS), essential for stem cell maintenance, is expressed in organizing center of meristems. The F. vesca homolog FvWUS1 exhibited a broader expression domain in young strawberry flowers than its Arabidopsis counterpart. Altogether, this work provides a valuable data resource for dissecting gene regulatory networks operating in different meristematic tissues in strawberry.